On zeros of some composite functions - Rašytė, Jovita (Lietuvos matematikos rinkinys, 2011)
We obtain an estimate of the number of zeros for the function F(zeta(s + i mh)), where zeta(s) is the Riemann zeta-function, and F : H(D)–>  H(D) is a continuous function,  D = {s ꞓ C: 1/2  < sigma < 1}.
Keywords: Riemann zeta-function; universality